2021
DOI: 10.11606/s1518-8787.2021055003461
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity combined with sedentary behaviour in the risk of mortality in older adults

Abstract: OBJECTIVE To examine the effects of physical activity (PA) and sedentary behaviour (SB), in isolation and combination, on all-cause mortality in older adults. METHODS Prospective, population-based cohort study. The data were collected from first wave in 2015 and the follow-up continued until 2020. The sample consisted of 332 older adult people aged ≥ 60 years-old, out of which 59 died. The level of PA and SB was assessed by the International Physical Activity Questionnaire (IPAQ). The older adults were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…For instance, a meta-analysis of individual data revealed that the effect of sedentary time on all-cause mortality was greater among those with lower levels of physical compared with those with higher levels of physical activity (HR: 1.46 vs 1.16, respectively) [ 23 ]. In addition, and in agreement with our results, the combined association between higher levels of physical inactivity and a longer time spent in sedentary behavior increased the risk of mortality compared to the most active groups in older adults [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…For instance, a meta-analysis of individual data revealed that the effect of sedentary time on all-cause mortality was greater among those with lower levels of physical compared with those with higher levels of physical activity (HR: 1.46 vs 1.16, respectively) [ 23 ]. In addition, and in agreement with our results, the combined association between higher levels of physical inactivity and a longer time spent in sedentary behavior increased the risk of mortality compared to the most active groups in older adults [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Another population-based longitudinal investigation revealed an increased risk of morbidity [68], and mortality for older adults who showed a rapid decline in GS [69,70]. In a population-based cohort study conducted with older adult Brazilians (>60 years; n = 332) to assess the relationship between PA and SB with mortality revealed SB as a potential risk for mortality [71]. Moreover, the analysis pointed to SB as a barrier for older adults to present moderate to vigorous PA levels.…”
Section: Discussionmentioning
confidence: 95%
“…The total time spent in moderate-to-vigorous-intensity physical activity (MVPA) per day was determined using the following formula: time spent in MVPA/day = [total minutes in moderate-intensity physical activity/week + (total minutes in vigorous-intensity physical activity/week × 2)]/7. 29 …”
Section: Methodsmentioning
confidence: 99%